Enhance the cropping intensity through crop diversification - Singh, R K; Sharma, D P; Gupta, Pramod (Indian Farming, 2023)
Under erratic climatic situations, the cropping intensity can be increased from existing 155 to 200–300% in the farmer’s field by the adoption of a new cropping pattern (Toria and Muskmelon) with a short duration variety and less water requirement crops along with advanced production techniques in the place of traditional cropping pattern. In this situation, KVK Chhatarpur has introduced short duration variety of Toria (RVT1) which is sown after the harvest or failure of kharif (summer) crop and muskmelon variety (Hara Madhu) which is sown after the harvest of Toria crop. It increases the cropping intensity which would lead to increase in the production of oil seeds and fruits under the deficit moisture condition. Temporary raised and sunkin beds are the new techniques for growing muskmelon during the zaid season for enhancing the production and productivity per unit area by less consumption of water. Therefore, this system generates additional income for farmers by maximizing the production per unit area and, utilizing the vacant space.